Sarawak Tourism Board contributions on revenue generation and job creation to the Sarawak: a sase study / Teddy Edwin Chapun - Chapun, Teddy Edwin (2003)
The tourism industry in Sarawak is experiencing rapid growth since the last few years, resulting from the year by year increasing arrival of visitors to Sarawak. In fafl the tourism industry has also become a major sector in contributing revenue to the Sarawak State and at the same time creating more job opportunities for Sarawakians, Sarawak Tourism Board (STB) was set up in July 1995, as the result Of the Sarawak Tourism Master Plan (STMP) for the pericxi 1995 to 2010, STE manages the promotion and marketing of Sarawak on behalf of State Ministry of Tourism STB's marketing focus is to promote Sarawak as a clean, safe. Friendly and adventurous destination, offering the "hidden paradise" of aomeo in terms of culture adventure and nature.